Washington! - Ross, Dana Fuller (Toronto New York Bantam Books, 1982)
Toby Holt, a wounded Civil War veteran, moves West to claim a homestead in Washington, disastrously marries a scheming woman, and encounters profiteers eager to steal his land
"Bantam advance reading copy"--Cover.
89577
Keywords: Frontier and pioneer life -- Fiction